Investigating the Growth of Algae Under Low Atmospheric Pressures for Potential Food and Oxygen Production on Mars - Cycil, Leena M.; Hausrath, Elisabeth M.; Ming, Douglas W.; Adcock, Christopher T.; Raymond, James; Remias, Daniel; Ruemmele, Warren P. (Frontiers in Microbiology, 2021)
With long-term missions to Mars and beyond that would not allow resupply, a self-sustaining Bioregenerative Life Support System (BLSS) is essential. Algae are promising candidates for BLSS due to their completely edible biomass, fast growth rates and ease of handling. Extremophilic algae such as snow algae and halophilic algae may also be especially suited for a BLSS because of their ability to grow under extreme conditions. However, as indicated from over 50 prior space studies examining algal growth, little is known about the growth of algae at close to Mars-relevant pressures. Here, we explored the potential for five algae species to produce oxygen and food under low-pressure conditions relevant to Mars. These included Chloromonas brevispina, Kremastochrysopsis austriaca, Dunaliella salina, Chlorella vulgaris, and Spirulina plantensis. The cultures were grown in duplicate in a low-pressure growth chamber at 670 ± 20 mbar, 330 ± 20 mbar, 160 ± 20 mbar, and 80 ± 2.5 mbar pressures under continuous light exposure (62-70 µmol m-2 s-1). The atmosphere was evacuated and purged with CO2 after sampling each week. Growth experiments showed that D. salina, C. brevispina, and C. vulgaris were the best candidates to be used for BLSS at low pressure. The highest carrying capacities for each species under low pressure conditions were achieved by D. salina at 160 mbar (30.0 ± 4.6 ×105 cells/ml), followed by C. brevispina at 330 mbar (19.8 ± 0.9 ×105 cells/ml) and C. vulgaris at 160 mbar (13.0 ± 1.5 ×105 cells/ml). C. brevispina, D. salina, and C. vulgaris all also displayed substantial growth at the lowest tested pressure of 80 mbar reaching concentrations of 43.4 ± 2.5 ×104, 15.8 ± 1.3 ×104, and 57.1 ± 4.5×104 cells per ml, respectively. These results indicate that these species are promising candidates for the development of a Mars-based BLSS using low pressure (~200-300 mbar) greenhouses and inflatable structures that have already been conceptualized and designed.